COVID-19: FAQs—Congenital Heart Surgery Recovery and Defining a "New Normal". Issue 5 (September 2020) - Dearani, Joseph A.; Stephens, Elizabeth H.; Guleserian, Kristine J.; Overman, David M.; Backer, Carl L.; Romano, Jennifer C.; Louis, James D. St; Sarris, George E.; Bacha, Emile; Tweddell, James S.
As recovery of congenital heart surgery programs begins during this COVID-19 pandemic, we review key considerations such as screening, protection of patients and health care workers (HCWs), case prioritization, barriers to reactivation, redesign of patient care teams, contribution of telemedicine, modification of trainees' experiences, preparation for potential resurgence, and strategies to maintain HCW wellness. COVID-19 has tested the resolve and grit of our specialty and we have an opportunity to emerge more refined.